A silicon carbide substrate with stepped stress distribution
By designing the stepped stress interval in the silicon carbide substrate, the problems of lattice distortion and stress unevenness are solved, the quality of the substrate and epitaxial sheet is improved, and the application range is expanded.
Patent Information
- Application Number
- CN202310837065.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-08-29
- Estimated Expiration
- 2043-07-07
AI Technical Summary
During the growth process, silicon carbide single crystal substrates are prone to introduce defects such as polycrystalline, polytype, microtube, and dislocation, resulting in lattice distortion and uneven stress, affecting crystal quality and the production and processing of downstream products.
A silicon carbide substrate with stepped stress distribution is designed, which is divided into the first gradient stress interval, the second gradient stress interval and the third gradient stress interval. Through the uniformly transitioned stress distribution, lattice distortion is eliminated and the substrate quality is improved.
The stress uniformity and crystal quality of the silicon carbide substrate are improved, the scope of use is expanded, and the production quality of epitaxial sheets or crystals is improved.
Smart Images

Figure CN119265695B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a silicon carbide substrate with a stepped stress distribution, belonging to the technical field of silicon carbide production and processing. Background Art
[0002] Silicon carbide (SiC) single crystal substrates have become the preferred semiconductor material for the fabrication of GaN-based high-frequency microwave devices due to their excellent physical properties, including a wide bandgap, high resistivity and thermal conductivity, and a strong breakdown field. With the continuous development of 5G technology, the market demand for SiC single crystal substrates continues to expand. More importantly, large-scale commercial applications have also placed higher quality requirements on SiC single crystal substrates.
[0003] During the growth process of silicon carbide crystals, various defects such as polycrystalline, polymorphic, micropipes, and dislocations are easily introduced into the crystal due to Si / C ratio imbalance, impurity introduction, and temperature gradient changes. Defects will cause lattice distortion, and more seriously, the crystal form will change, such as the generation of polymorphic symbiosis such as 4H, 6H, 3C, and 15R. Lattice distortion releases stress by generating defects, that is, introducing internal stress in silicon carbide, thereby reducing the crystal quality of silicon carbide, limiting the scope of use of the crystal, and reducing the yield rate of the product; and the internal stress of the silicon carbide substrate is prone to uneven stress distribution due to the existence of temperature fields or defects, thereby affecting the production and processing of downstream products. Summary of the Invention
[0004] To address the above-mentioned problems, a silicon carbide substrate with a stepped stress distribution is provided. The silicon carbide substrate is divided into a first gradient stress interval, a second gradient stress interval, and a third gradient stress interval. The relative stress in each area transitions uniformly and achieves a stepped distribution. This can improve the quality of the silicon carbide substrate and expand the scope of use of the silicon carbide substrate. The silicon carbide substrate can be used to process epitaxial wafers or serve as a seed crystal for growing crystals, thereby reducing the stress of epitaxial wafers or crystals to obtain high-quality epitaxial wafers or crystals.
[0005] According to one aspect of the present application, a silicon carbide substrate having a stepped stress distribution is provided, wherein the diameter of the silicon carbide substrate is greater than 150 mm, and the silicon carbide substrate includes a first main surface and a second main surface;
[0006] The first major surface has a first gradient stress zone, a second gradient stress zone surrounding the first gradient stress zone, and a third gradient stress zone surrounding the second gradient stress zone, wherein the width of the third gradient stress zone extending inward from the edge of the substrate is 2.5-30 mm, and the width of the second gradient stress zone extending inward from the edge of the third gradient stress zone is 10-50 mm;
[0007] The internal relative stress in the first gradient stress interval is greater than or equal to the internal relative stress in the second gradient stress interval, and less than the internal relative stress in the third gradient stress interval. The internal relative stress is a stress value measured vertically extending at least 3 μm from the first main surface or the second main surface into the silicon carbide substrate.
[0008] The relative internal stress in the second gradient stress interval is the smallest, and the relative internal stress in the third gradient stress interval is the largest. Therefore, the wider the width of the second gradient stress interval extending inward from the edge of the third gradient stress interval is, the greater the proportion of the area with smaller relative internal stress in the silicon carbide substrate.
[0009] Since the silicon carbide crystal is grown in a crucible, the periphery of the silicon carbide crystal will contact the graphite crucible. In the high-temperature environment of crystal growth, the graphite crucible will expand due to heat, which will squeeze the edge of the silicon carbide crystal and cause edge stress, which is easy to cause lattice distortion and thus stress. When the silicon carbide crystal is processed to obtain a silicon carbide substrate, the stress in the third gradient stress interval of the substrate is the largest, and the first gradient stress interval is the central area of the crystal. Since there is a radial temperature gradient in the SiC crystal growth, and the radial temperature gradient increases from the center to the edge, the overall relative stress gradually increases from the center to the edge. Therefore, the stress shows a trend of gradually increasing from the center to the edge. The stress in the first gradient stress interval is greater than that in the second gradient stress interval.
[0010] Optionally, the in-vivo absolute stress in the second gradient stress interval is greater than or equal to the in-vivo absolute stress in the first gradient stress interval, and less than the in-vivo absolute stress in the third gradient stress interval, where the in-vivo absolute stress is a stress value measured vertically extending at least 3 μm from the first main surface or the second main surface into the silicon carbide substrate;
[0011] Depending on the processing state of the SiC substrate, the in-body absolute stress and in-body relative stress are stress values measured at a point extending vertically at least 3 μm from the first main surface or the second main surface into the silicon carbide substrate. This ensures that the obtained stress value is the in-body stress value of the SiC substrate, eliminating the stress introduced into the SiC substrate during cutting, grinding, polishing and other processes.
[0012] Optionally, at any plane parallel to the first main surface and / or the second main surface, the radial internal absolute stress in the first gradient stress interval is -20 to 5 MPa, the radial internal absolute stress in the second gradient stress interval is 5 to 15 MPa, and the radial internal absolute stress in the third gradient stress interval is 15.2 to 50 MPa.
[0013] Preferably, at any plane parallel to the first main surface and / or the second main surface, the radial internal absolute stress in the first gradient stress interval is -5 to 5 MPa, the radial internal absolute stress in the second gradient stress interval is 5 to 10 MPa, and the radial internal absolute stress in the third gradient stress interval is 15.2 to 20 MPa.
[0014] Because the internal tensile and compressive stresses of the silicon carbide substrate cause the interplanar spacing d to expand and contract accordingly, when Raman is used to test stress, the Raman peak intensity will shift to low or high frequencies. When the substrate is subjected to tensile stress, the Raman peak shifts to low frequencies, and the resulting stress value is positive. When the substrate is subjected to compressive stress, the Raman peak shifts to high frequencies, and the resulting stress value is negative. Therefore, the positive and negative before the stress value in this application represent the force direction inside the substrate, and the absolute value of the value represents the magnitude of the stress. For example, if the average absolute stress in the first gradient of the silicon carbide substrate is -3MPa and the average absolute stress in the second gradient is 5MPa, then the absolute stress in the first gradient stress interval is compressive stress, the absolute stress in the second gradient stress interval is tensile stress, and the radial absolute pressure in the first gradient stress interval is less than the radial absolute pressure in the second gradient stress interval.
[0015] According to the radial internal absolute stress values in the first, second, and third gradient stress intervals, the first gradient stress interval is a transition region between compressive stress and tensile stress, while the second and third gradient stress intervals are both tensile stress regions. The closer the value of the first or third gradient stress interval is to that of the second gradient stress interval, the more uniform the radial internal stress distribution of the silicon carbide substrate.
[0016] Optionally, an axial test is performed from any point on the first main surface extending vertically into the silicon carbide substrate, and the axial absolute stress in the first gradient stress interval is -30 to 10 MPa, the axial absolute stress in the second gradient stress interval is 10 to 30 MPa, and the axial absolute stress in the third gradient stress interval is 30.2 to 50 MPa.
[0017] The reference value of absolute stress in this application is the reference stress calculated based on the standard Raman peak position obtained from the perfect lattice parameters of SiC, and is marked as 0.
[0018] Optionally, at any plane parallel to the first main surface and / or the second main surface, the radial internal relative stress in the first gradient stress interval is -15 to 15 MPa, preferably -14.3 to 14.5 MPa, the radial internal relative stress in the second gradient stress interval is -10 to 10 MPa, preferably -9.4 to 10.0 MPa, and the radial internal relative stress in the third gradient stress interval is -24.8 to 24.8 MPa.
[0019] The radial internal absolute stress can reflect the difference between the substrate and a substrate without residual stress in the body (ie, a perfect crystal), and the radial internal relative stress can reflect the uniformity and distribution of the substrate in the radial direction.
[0020] Optionally, at any plane parallel to the first major surface and / or the second major surface, S max1 represents the maximum absolute value of the relative stress in the radial body within the first gradient stress interval, S max2 represents the maximum absolute value of the relative stress in the radial body within the second gradient stress interval, S max3 Represents the maximum absolute value of the relative stress in the radial body within the third gradient stress interval, △S1=S max1 -S max2 , △S2=S max3 -S max1 , △S1≤△S2;
[0021] Preferably, 0MPa≤ΔS1≤10MPa, 0MPa≤ΔS2≤22MPa.
[0022] Preferably, 0.2MPa≤ΔS1≤9.8MPa, 0.3MPa≤ΔS2≤21.4MPa.
[0023] Optionally, at any plane parallel to the first major surface and / or the second major surface, S min1 represents the minimum absolute value of the relative stress in the radial body within the first gradient stress interval, S min2 represents the minimum absolute value of the relative stress in the radial body within the second gradient stress interval, S min3 Represents the minimum absolute value of the relative stress in the radial body within the third gradient stress interval, △S3=S min1 -S min2 , △S4=S min3 -S min1 , △S3≤△S4;
[0024] Preferably, 0MPa≤ΔS3≤5MPa, 0MPa≤ΔS4≤20MPa.
[0025] Preferably, 0.2MPa≤ΔS3≤4.7MPa, 0.3MPa≤ΔS4≤19.6MPa.
[0026] The absolute values of the radial internal relative stress represent the relative stress magnitudes within each region. ΔS1 and ΔS3 represent the difference in radial internal relative stress between the second gradient stress interval and the first gradient stress interval. The smaller the ΔS1 and ΔS3 values, the closer the radial internal relative stresses are in the second and first gradient stress intervals. ΔS2 and ΔS4 represent the difference in radial internal relative stress between the third gradient stress interval and the first gradient stress interval. The smaller the ΔS2 and ΔS4 values, the closer the radial internal relative stresses are in the third and first gradient stress intervals. When ΔS1 ≤ ΔS2 and ΔS3 ≤ ΔS4, the difference in radial internal relative stress between the second and first gradient stress intervals is smaller than the difference between the third and first gradient stress intervals.
[0027] Optionally, at any plane parallel to the first main surface and / or the second main surface, S1 represents the average absolute value of the radial internal relative stress in the first gradient stress interval, S2 represents the average absolute value of the radial internal relative stress in the second gradient stress interval, and S3 represents the average absolute value of the radial internal relative stress in the third gradient stress interval, 0MPa≤S1-S2≤14.5MPa, 0MPa≤S3-S1≤22.5MPa, and preferably, 0MPa≤S3-S1≤22.4MPa.
[0028] The silicon carbide substrate is subjected to multi-point stress detection. The above-mentioned average absolute value refers to the value obtained by dividing the sum of the absolute values of stress at all detection points in the area by the number of detection points. The multi-point detection can be performed by selecting multiple points at different positions in the area for detection, or by performing a mapping test on the substrate.
[0029] Preferably, 0MPa≤S1-S2≤8MPa, 0MPa≤S3-S1≤10MPa.
[0030] Optionally, an axial test is performed from any point on the first main surface extending vertically into the silicon carbide substrate, and the axial relative stress in the first gradient stress interval is -20 to 20 MPa, preferably -19.3 to 19.7 MPa, the axial relative stress in the second gradient stress interval is -16 to 16 MPa, preferably -15.7 to 15.2 MPa, and the axial relative stress in the third gradient stress interval is -25 to 25 MPa, preferably -24.3 to 24.7 MPa.
[0031] The axial absolute stress can reflect the difference between the substrate and the stress-free substrate in the body, and the axial relative stress can reflect the uniformity of the substrate in the axial direction.
[0032] In this application, the radial internal relative stress in the first gradient stress interval is calculated based on a baseline value within the first gradient region as a whole. The relative stress value at each test point is then calculated by performing a numerical calculation relative to the baseline value. This baseline value includes, but is not limited to, the median, mean, mode, or other statistical function calculation results of all stress values in the entire test region. Similarly, the radial internal relative stress in the second and third gradient stress intervals is calculated using the same method.
[0033] The reference values of the radial body absolute stress in the first gradient stress interval, the second gradient stress interval, and the third gradient stress interval are the reference stresses calculated based on the standard Raman peak positions obtained from the perfect lattice parameters of SiC, and are marked as 0.
[0034] Optionally, an axial test is performed by extending vertically from any point on the first main surface into the silicon carbide substrate, S max5 It is recorded as the maximum relative stress in the axial body in the first gradient stress interval, S min5 It is recorded as the minimum relative stress in the axial body in the first gradient stress interval, △S5=S max5 -S min5 , 0MPa≤ΔS5≤10MPa, preferably 0MPa≤ΔS5≤9.6MPa;
[0035] S max6 It is recorded as the maximum relative stress in the axial body in the second gradient stress interval, S min6 It is recorded as the minimum relative stress in the axial body in the second gradient stress interval, △S6=S max6 -S min6 , 0MPa≤△S6≤10MPa, preferably 0MPa≤△S6≤9.2MPa;
[0036] S max7 It is recorded as the maximum relative stress in the axial body in the third gradient stress interval, S min7 It is recorded as the minimum relative stress in the axial body in the third gradient stress interval, △S7=S max7 -S min7 , 0MPa≤ΔS7≤10MPa, preferably 0MPa≤ΔS7≤9.9MPa;
[0037] The above-mentioned maximum value and minimum value of the axial internal relative stress are the true values of the axial internal relative stress, and compressive stress and tensile stress are distinguished in the axial direction. For example, on any axis, the axial internal relative stress in the first gradient stress interval is -5~1MPa, then the maximum value of the axial internal relative stress is 1MPa, and the minimum value of the axial internal relative stress is -5MPa, and △S5 is 6MPa. △S5, △S6 and △S7 represent the degree of change between the axial crystal plane spacing of the substrate at the microscopic level. The smaller the above-mentioned △S5, △S6 and △S7 are, the smaller the change in the axial crystal plane spacing of the substrate is.
[0038] Preferably, 0MPa≤△S5≤5.2MPa, 0MPa≤△S6≤3.9MPa, 0MPa≤△S7≤6.1MPa.
[0039] Optionally, the diameter of the silicon carbide substrate is greater than 200 mm, the width of the third gradient stress interval extending inward from the edge of the substrate is 21-30 mm, and the width of the second gradient stress interval extending inward from the edge of the third gradient stress interval is 10-39 mm; and / or
[0040] The thickness of the silicon carbide substrate is not less than 0.1 mm.
[0041] Optionally, an off angle of the first major surface and / or the second major surface relative to the {0001} plane is less than 4°.
[0042] Optionally, the curvature of the silicon carbide substrate is -50 μm to 50 μm, preferably -20 μm to 20 μm, and more preferably -10 μm to 10 μm.
[0043] Optionally, the crystal form of the silicon carbide substrate is one of 2H-SiC, 4H-SiC, 6H-SiC, 3C-SiC, and 15R-SiC, preferably 4H-SiC.
[0044] Optionally, the silicon carbide substrate is a semi-insulating silicon carbide substrate or a conductive silicon carbide substrate.
[0045] Optionally, the local thickness deviation of the first gradient stress interval is 0.1-0.3 μm, the local thickness deviation of the second gradient stress interval is 0.3-0.7 μm, and the local thickness deviation of the third gradient stress interval is 0.7-2 μm.
[0046] The silicon carbide substrate described in any of the above items is made by processing a silicon carbide single crystal. According to another aspect of the present application, a method for preparing a silicon carbide single crystal is provided, comprising the following steps:
[0047] (1) Adding silicon carbide powder into a graphite crucible;
[0048] (2) Vacuum the furnace to 10 -6 mbar, then introduce high-purity inert gas to 300-500 mbar, repeat this process 2-3 times, and finally evacuate the furnace to 10 -6 mbar or less;
[0049] (3) High-purity inert gas is introduced into the furnace body, and the pressure is raised to 10-100 mbar within 1-3 hours. The high-purity inert gas is continuously introduced and the pressure is maintained constant;
[0050] (4) Crystal growth stage: While maintaining the pressure constant, the temperature inside the furnace is raised to the single crystal growth temperature of 2200K-2800K within 3-5 hours, and the growth time is 30-150 hours;
[0051] (5) After the single crystal growth is completed, open the furnace body and take out the graphite crucible to obtain the silicon carbide single crystal.
[0052] Optionally, the graphite crucible is coated with a composite coating, and the composite coating comprises:
[0053] Ta x C y The permeation layer, the Ta x C y The infiltration layer is deposited on the graphite substrate, where 0 <x<1,0<y<1;
[0054] TaC coating, the TaC coating is coated on the Ta x C y On the permeation layer.
[0055] The Ta x C y The permeation layer is formed on the surface and inside of the graphite substrate. x C y The infiltration layer is evenly distributed on the surface of the graphite substrate and has good density, which improves the environmental stability of the silicon carbide crystal during the growth process and reduces the thermal expansion of the graphite substrate.
[0056] Optionally, the Ta x C y Ta in the permeate layer x C y The grains grow anisotropically, and the TaC grains in the TaC coating grow along the
[200] and
[220] directions; the Ta x C y Ta in the permeate layer x C y The TaC grains and the TaC grains in the TaC coating are arranged in a staggered manner. x C yTa in the permeate layer x C y The grains are arranged in a staggered manner. x C y The size of the grains is 5-30 μm; the TaC grains in the TaC coating are arranged in a stacking and staggered manner, and the size of the TaC grains is 15-40 μm.
[0057] Ta x C y The grain size can reduce the Ta x C y Stress in the penetration layer, avoid Ta x C y The formation of the infiltration layer forms a clear grain boundary and avoids Ta x C y The generation of cracks in the infiltration layer prevents the graphite substrate from squeezing the crystal.
[0058] The TaC grains in the TaC coating grow in an oriented manner along the
[200] and
[220] directions, which can improve the density of the TaC coating, thereby improving the bonding strength between the composite coating and the graphite substrate, as well as the temperature resistance and thermal chemical corrosion resistance of the composite coating, thereby reducing the interference of the graphite substrate in the crystal growth process, and facilitating the preparation of silicon carbide crystals with uniform quality.
[0059] Optionally, the Ta x C y The thickness of the permeation layer is 10-450 μm, the thickness of the TaC coating is 30-400 μm, and the Ta x C y The total thickness of the permeation layer and the TaC coating is 40-500 μm.
[0060] The beneficial effects of this application include but are not limited to:
[0061] 1. The stress introduced by temperature gradient changes or changes in the crystal growth environment during the growth of silicon carbide crystals is the internal stress of the silicon carbide substrate. The silicon carbide substrate of the present application has a compressive stress region in the first gradient stress interval, a stress transition region in the second gradient stress interval, and a tensile stress region in the third gradient stress interval, thereby obtaining a silicon carbide substrate with a stepped stress distribution.
[0062] 2. The radial internal stress and axial internal stress of the silicon carbide substrate of the present application are relatively low in the first gradient stress interval, the second gradient stress interval and the third gradient stress interval, and the stress distribution is uniform in the above-mentioned areas, and a uniform stress transition can be achieved at the junction of the areas, which proves that the silicon carbide substrate has good uniformity and can be used as an epitaxial substrate or seed crystal, which is beneficial to improving the production quality of downstream products.
[0063] 3. According to the silicon carbide substrate of the present application, the stress values tested in different areas can be used to understand the changes in the lattice in different areas. The stress values can be used to analyze the microscopic unit cell parameters of the substrate, thereby playing a certain feedback role and facilitating the mass production of high-quality silicon carbide substrates.
[0064] 4. The present application utilizes a composite coating formed on the crucible surface to improve the tolerance of the graphite crucible and reduce the impact of the graphite crucible on the crystal growth process, thereby improving the stability of the crystal environment and the uniformity of the temperature field, and reducing the number of defects and impurity content in the crystal, thereby preparing high-quality silicon carbide crystals with a stepped stress distribution.
[0065] 5. According to the stress distribution in various regions of the silicon carbide substrate of the present application, it can be adjusted according to the parameters of each process in crystal growth to prepare a high-quality silicon carbide substrate. Moreover, through the quantitative testing method of the present application, the detected stress also includes the stress in the substrate caused by lattice distortion that has not yet been released through defects, thereby improving the detection accuracy of stress in the silicon carbide substrate and reflecting the entire stress information of the entire silicon carbide substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0067] Figure 1 Schematic diagram of the Raman equidistant focusing test of the internal stress of the substrate involved in Example 4 of the present application.
[0068] Figure 2 Schematic diagram of the Raman isofocusing plane test of the internal stress of the substrate involved in Example 4 of the present application.
[0069] Figure 3 This is an SEM image of the surface of crucible 1# involved in Example 5 of the present application. DETAILED DESCRIPTION
[0070] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0071] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0072] The Raman method used in the following embodiments to measure substrate stress is as follows: A Raman spectrometer uses a monochromatic laser of a certain wavelength to pass through a series of optical paths before being focused by an objective lens onto the substrate surface. The laser photons interact with the substrate's crystal lattice, causing photon scattering. Raman scattering occurs due to the lattice vibrations of the substrate itself. When residual stress exists within the sample, tensile or compressive stresses cause atomic bond lengths to lengthen or shorten, resulting in a decrease or increase in the atomic vibration frequency. This is reflected in the Raman spectrum as a shift in the substrate's characteristic peak toward lower or higher frequencies, known as a peak shift.
[0073] Example 1 Quantitative Testing Method for Substrate Stress
[0074] (1) Calculation of peak position offset and stress conversion coefficient
[0075] First, a single crystal XRD diffractometer is used to test the silicon carbide substrate and the substrate is analyzed based on the reciprocal lattice space. The parameters of the standard 4H-silicon carbide substrate are calculated and compared with the standard parameters. Then, according to the Bragg diffraction equation: 2dsinθ=nλ, where d is the interplanar spacing, θ is the diffraction half-angle, n is the diffraction order, and λ is the wavelength, the θ and d of different substrates are tested. It can be seen that the tensile and compressive stress inside the crystal causes the interplanar spacing d to undergo corresponding expansion and contraction changes. According to the different interplanar spacings d0 and d x , d x It is divided into d1 and d2, where d0 is the theoretical interplanar spacing, d1 is the interplanar spacing after tensile stress, and d1 is greater than d0; d2 is the interplanar spacing after compressive stress, and d2 is less than d0. The interplanar spacing difference △d at different positions is calculated, △d=d1-d0 or △d=d0-d2.
[0076] The actual peak position of the substrate is obtained according to the Raman test, and the peak position offset △v at different test points is calculated compared with the standard peak position; the stress value σ of the silicon carbide substrate at different test points is calculated in combination with Hooke's law or the stress-strain formula. The ratio of the peak position offset to the stress value at different test points is the peak position offset to stress conversion coefficient μ, which ranges from -125 to -2500.
[0077] The calculation formula of Hooke's law is σ / S=E×(△d / d0), where S is the area affected by σ, which is a fixed value. When Hooke's law is applicable to microscopic calculations, S is the microscopic area, which can be calculated as unit 1. E is the Young's modulus of the substrate, which is a fixed parameter of the substrate. △d is the difference in crystal plane spacing at different positions, d0 is the theoretical crystal plane spacing, and σ is the stress value that needs to be calculated.
[0078] The calculation formula for stress and strain is σ=E×△d, where E is the Young's modulus of the substrate, which is a fixed parameter of the substrate, △d is the difference in crystal plane spacing at different positions, and σ is the stress value to be calculated.
[0079] (2) Quantitative test method of substrate stress
[0080] First, set the Raman test points. You can perform single-point testing or a mapping scan of the entire substrate. Single-point testing involves setting up scattered coordinate points, while mapping scans range from 10x10 to 50x50 or more points. You can choose the appropriate test method based on the properties of the substrate to determine the Raman test coordinate diagram for the silicon carbide substrate.
[0081] The test results are then output, including but not limited to editable peak positions, peak intensity data, and mapping.
[0082] The output data is then subjected to peak position fitting, with fitting functions including but not limited to Gaussian, Lorentz, GaussLor, AGauss, Aloren, and AGaussLor, to obtain precise peak position values and peak position offsets, with the peak position accurate to at least one decimal place.
[0083] Finally, according to the peak shift and stress conversion coefficient μ calculated in (1) and the peak shift △v obtained in the Raman test, the stress value of silicon carbide is calculated as follows: σ (MPa) = μ × △v (cm -1 ), and finally obtain the stress test image of the substrate.
[0084] Example 2: Test of curvature of substrate surface
[0085] Because SiC wafers undergo extensive mechanical stress during the series of processing steps from crystals to wafers, it's difficult to ensure a perfectly flat surface, resulting in a certain degree of warpage. To eliminate the impact of substrate surface curvature on surface and internal stress measurements, a substrate curvature test is performed. Based on this curvature, the substrate surface stress is tested using equidistant focus testing, while internal stress is tested using either equidistant focus testing or equifocal plane testing.
[0086] After the curvature test, the tester needs to be calibrated using single crystal silicon. First, a Z-axis mapping test is performed on the single crystal Si to confirm that it is a Gaussian distribution. With the surface of the single crystal Si substrate as the zero point, an axial mapping test is performed from -100μm inside the single crystal Si substrate to +20μm above the single crystal Si substrate to analyze the change in Raman signal intensity. The single crystal Si substrate is a non-transparent material, so its peak intensity presents a Gaussian distribution with the surface zero point position as the symmetry axis. Then, a surface focusing single point test is performed on the single crystal Si. The instrument is calibrated to make the single crystal Si Raman peak position 520.70cm -1 At this point, it indicates that the instrument optical path has been calibrated.
[0087] A calibrated tester was used to test the 4H-SiC substrate in the Z direction. The Raman laser was directed from -100μm inside the 4H-SiC substrate to +20μm above the 4H-SiC substrate. 4H-SiC substrates and other silicon carbides are transparent materials, allowing the Raman laser to penetrate deep into the substrate. The feedback signal gradually weakened as the Raman laser's penetration depth increased. Other silicon carbides, including semi-insulating and conductive silicon carbide substrates and those with different crystal forms such as 3C, 4H, 15R, and 6H, exhibited a Raman peak intensity that gradually decreased as the laser's penetration depth increased.
[0088] The Raman instrument's autofocus function can automatically find the strongest peak of the test signal on the substrate surface, thereby enabling the measurement of the substrate surface curvature. The specific method is as follows:
[0089] S1: First, ensure that the test platform is level, select a fixed origin (0,0) on the test platform, and mark this point as the three-dimensional coordinate (0,0,0);
[0090] S2: Raise the objective lens to a height that does not contact the substrate according to the thickness of the substrate, and automatically focus on any point on the substrate surface where the test signal is strongest. Mark this position as (a, b, c). Then adjust the Raman laser downward by a distance H and focus on the position (a, b, cH).
[0091] S3: Adjust the Raman laser test position to (0,0,cH) to perform an isofocusing plane test to obtain a two-dimensional peak intensity scan of the substrate surface. Based on the peak intensity distribution relationship of the silicon carbide substrate and the two-dimensional peak intensity scan of the substrate surface, the distance between the focal plane of the Raman laser and the surface of the silicon carbide substrate can be obtained, thereby obtaining the in-plane curvature of the substrate and obtaining the in-plane curvature distribution map of the substrate.
[0092] Example 3 Axial Test to Distinguish Substrate Surface Stress from Internal Stress
[0093] Since the substrate is affected by the temperature field and the introduction of inclusions during the crystal growth process, thermal stress and residual stress exist inside the crystal. The substrate is obtained after a series of cutting, grinding and polishing. The above-mentioned processing of the crystal into the substrate will cause surface lattice distortion, thereby generating surface stress. In order to further distinguish the surface stress from the internal stress of the substrate, according to the transmittance characteristics of silicon carbide, the substrate is subjected to axial testing, namely Z-direction mapping, with the substrate surface as the zero point. The test range of the axial test is from -150μm to -30μm inside the substrate to above the substrate surface.
[0094] During the test, the laser spot was gradually focused upward from the substrate body to the damaged stress extension layer, then to the surface damaged layer, and then continued upward into the air to determine the thickness of the substrate surface damaged layer and the damaged stress extension layer. With the substrate surface as the zero point, the axial test range was from -100μm inside the substrate to 30μm above the substrate surface. Five points on the substrate were tested, top, bottom, left, and right. All five points on the substrate showed the same trend, with only the maximum negative stress at the surface damage point showing a difference.
[0095] When the laser spot moves from -100μm inside the substrate to -30μm, the stress fluctuates along the horizontal line, indicating that the internal stress is uniform. When the laser spot is focused on the damaged stress extension layer, the stress curve begins to show a downward trend at -30μm, and the stress downward trend gradually increases. When it approaches the zero point on the substrate surface, it reaches a negative stress maximum, which is the stress value of the surface damage layer. Finally, the laser spot continues to move upward and gradually leaves the substrate surface into the air, and the stress shows a rapid rise to chaotic fluctuations. Therefore, the thickness of the substrate's surface damage layer and the damaged stress extension layer can be determined based on the substrate's axial test results, thereby distinguishing the stress in the substrate into surface stress and internal stress, providing a theoretical basis for subsequent quantitative testing of surface stress and internal stress in the substrate.
[0096] Example 4 Quantitative Testing of Stress in the Substrate
[0097] During the PVT crystal growth process, silicon carbide is affected by temperature gradient changes and the intrusion of inclusions, resulting in residual stress in the crystal. Different from the surface processing stress, the internal stress is located at a certain depth from the surface, reflecting the thermal stress and residual stress of the crystal growth. In addition, silicon carbide undergoes a large amount of external mechanical stress in the process of preparing the substrate from the crystal through a series of processing, and it is difficult to ensure that the surface is completely horizontal, that is, there is a certain degree of curvature on the surface of the substrate. According to the measurement method of the curvature of the substrate surface obtained by Raman testing in Example 2, this embodiment, combined with the physical properties of silicon carbide, relates to a method for quantitatively characterizing its internal stress that is not affected by surface curvature.
[0098] Based on the physical property of silicon carbide being light-transmissive, the Raman quantitative characterization method for substrate internal stress is divided into equidistant focusing test and equifocal plane test, as follows:
[0099] 1. Equally spaced focus test
[0100] The principle of equidistant focusing test is as follows Figure 1 As shown, Figure 1 (b) Schematic diagram of the focus of the Raman laser inside the substrate. Figure 1(a) is the test principle diagram. In this test mode, the focal depth (d) of the Raman laser focused into the substrate remains constant at different test points. First, the penetration depth (Dp) of the Raman laser is calculated according to the following formula:
[0101]
[0102] In the above formula, Dp is the penetration depth of Raman excitation in the sample, α is the absorption coefficient, λ is the laser wavelength, and k is the extinction coefficient. The specific value of the penetration depth (Dp) is calculated according to the above formula, and a suitable focal depth (d) is selected. The requirement that needs to be met is that the penetration depth (Dp) is greater than the focal depth (d). Since the test is for internal stress, the focal depth d needs to be greater than the thickness of the surface damage layer and the damage stress extension layer tested in Example 3.
[0103] The Raman laser spot diameter (D) is then calculated according to the following formula:
[0104] Where λ is the laser wavelength and Na is the numerical aperture of the device.
[0105] The spot diameter (D) is the minor axis diameter of the laser spot. The larger this value, the stronger the Raman peak intensity at each test position and the more impurity peaks there are, affecting the Raman detection accuracy. When λ is determined, if the Na value is large, the peak intensity is very weak, which will also affect the Raman detection accuracy. Therefore, it is necessary to select appropriate λ and Na to improve the accuracy of this test method.
[0106] According to the material properties of silicon carbide, the peak intensity reaches its highest when the laser is focused on the substrate surface. Therefore, the automatic focusing function of the Raman tester can be used to focus the laser on the substrate surface. Subsequently, according to the focus depth (d) determined above, equal-spaced focusing tests can be performed on different positions of the substrate, that is, the distance between the focusing plane and the substrate surface is always equal. This method is not affected by the bending and warping of the substrate surface, so that the obtained Raman peak intensity is always maintained at the axial maximum value at the test point. According to the stress quantitative testing method of Example 1, the in-vivo stress test diagram of the substrate is obtained.
[0107] 2. Equifocal plane test
[0108] The principle of isofocal plane test is as follows Figure 2 As shown, Figure 2 (b) Schematic diagram of the focus of the Raman laser inside the substrate. Figure 2(a) is the test principle diagram. Under this test method, the focal depth (d) of the Raman laser spot focused on the substrate changes at different test points. The laser spot at different test points is focused on the same plane inside the substrate. The penetration depth (Dp) of the Raman laser is calculated according to the same formula as the equidistant focusing test, and the appropriate focal depth (d) is selected using the same selection method.
[0109] Because the focal planes in this testing method are equal, and in conjunction with the characteristics of silicon carbide, the peak intensity reaches its highest when the laser is focused on the substrate surface and gradually decays with increasing focus depth. Furthermore, according to Raman tester measurements of the effective signal-to-noise ratio, it is found that the effective signal-to-noise ratio is inversely correlated with the Raman laser focus depth (d). Therefore, in this testing method, the focus depth (d) at different test points needs to be combined with the curvature of the substrate to obtain the effective peak position offset using the stress quantitative testing method of Example 1, thereby reducing the error in the in vivo stress test. This testing method produces an in vivo stress test result graph of the substrate.
[0110] Through the above two testing methods of equal spacing focusing and equal focal plane, the peak offset inside the substrate is obtained respectively, and the internal stress distribution of the substrate is calculated. The difference between the internal stress values of the substrate calculated by the equal spacing focusing test and the equal focal plane test is ≤0.2MPa, and the difference between the peak values obtained by the equal spacing focusing test and the equal focal plane test is <0.0005cm -1 The above two methods can verify the accuracy of the quantitative detection method of the present application, and the accuracy of the test method can be further improved according to the settings of the focus depth and the spot diameter.
[0111] The internal stress includes the internal absolute stress and the internal relative stress. Taking 4H-SiC as an example, it is explained as follows:
[0112] The absolute stress in the body is calculated by subtracting the measured 4H-SiC peak position from the standard peak position to determine the simplified wave vector peak position, such as FTO (2 / 4). The absolute stress in the body is calculated as follows:
[0113] σabsolute=μ×(v 实际 -V FTO(2 / 4) ), σ is in MPa, v 实际 and V FTO(2 / 4) The unit is cm -1 , where v 实际 is the actual FTO (2 / 4) peak position at the substrate test point, V FTO(2 / 4) is the standard peak position of FTO (2 / 4) of the substrate;
[0114] The relative stress in the body is calculated by taking the difference between the measured values of the same simplified wave vector peak position at any two points in the SiC substrate surface, such as the FTO (2 / 4) peak position. The formula for calculating the relative stress in the body is:
[0115] σrelative=μ×(v (x1,y1) -V (x2,y2) ), σ is in MPa, v (x1,y1) and V (x2,y2) The unit is cm -1 , where v (x1,y1) is the actual FTO (2 / 4) peak position at the substrate test point, V (x2,y2) is the actual FTO (2 / 4) peak position of the substrate relative point. The relative stress value of the test point is calculated according to the above calculation formula. If the relative value of σ is positive, it means that the stress of the test point relative to the relative point is tensile stress. If the relative value of σ is negative, it means that the stress of the test point relative to the relative point is compressive stress.
[0116] Example 5
[0117] This embodiment relates to a method for preparing a graphite crucible for growing silicon carbide, comprising the following steps:
[0118] 1) Soaking the graphite substrate in a tantalum pentachloride solution, wherein the concentration of tantalum pentachloride is 5%-95% and the porosity of the graphite substrate is 5%-55%, and performing gas pressure treatment, wherein the gas pressure is 1-2 MPa and the pressurization time is 0.5-1 h. The soaked graphite substrate is dried and calcined to obtain a graphite substrate with Ta x C y Graphite substrate of the infiltration layer;
[0119] 2) Prepare a slurry containing TaC, which includes: 25-40 parts of TaC powder, 20-35 parts of solvent, 15-25 parts of cosolvent, 1-3 parts of defoamer, 2-5 parts of thickener, 5-15 parts of straight-chain saturated aliphatic hydrocarbon, and 1-3 parts of carbon powder. Spray the slurry onto the surface with TaC. x C y The surface of the graphite substrate of the infiltration layer is dried and then sintered under an inert gas: sintering at 700-900 mbar and 500-700°C for 3-5 hours; then the pressure is increased to 1000-1100 mbar, the temperature is increased to 1600-1800°C, and sintering is carried out for 8-10 hours; finally, the pressure is increased to 145-155 kPa, the temperature is increased to 2200-2400°C, and sintering is carried out for 14-16 hours. Finally, the temperature is lowered to room temperature and normal pressure within 15-25 hours to obtain the graphite crucible.
[0120] Preferably, the calcination in step 1) is carried out under inert gas, and the dried graphite substrate is placed in a vacuum furnace for stepwise heating and stepwise cooling:
[0121] Stepwise heating: heating to 250-350℃, calcining for 4-6h, then heating to 850-950℃, calcining for 2.5-3.5h, and finally heating to 1200-1300℃, calcining for 3-5h;
[0122] Step cooling: cool to 900-1100℃, maintain for 0.5-2h, then cool to 750-850℃, maintain for 0.5-1h, and finally cool to room temperature at a cooling rate of 15-25℃ / h.
[0123] Preferably, the pressure in the vacuum furnace during the calcination process is 800-1000 mbar.
[0124] Crucibles 1#-6# and comparative crucibles D1#-D3# were prepared according to the above preparation method, as follows:
[0125] Crucible 1#
[0126] 1) placing a tantalum pentachloride n-butanol solution soaked with a graphite substrate in a container, wherein the concentration of tantalum pentachloride in the tantalum pentachloride n-butanol solution is 70%, and the porosity of the graphite substrate is 45%. The container is placed in a pressure chamber for pressurization treatment at a pressurization rate of 0.1 MPa / min. When the pressure in the pressure chamber reaches 1 MPa, the pressure is maintained for 1 hour, and then the pressure is released. The soaked graphite substrate is transferred to a vacuum furnace and dried at 60°C for 7 hours, and then placed in a vacuum furnace. Argon gas was introduced to maintain the pressure in the furnace at 900 mbar, and then calcination was carried out. The temperature was increased in steps: 1 hour to 300°C and calcined for 5 hours; then 2 hours to 900°C and calcined for 3 hours; finally 1 hour to 1250°C and calcined for 4 hours; then staged cooling was started: 1 hour to 1000°C and maintained for 1 hour, then 1 hour to 800°C and maintained for 1 hour, and finally cooled to room temperature at a rate of 20°C / h to obtain a graphite substrate with a TaxCy infiltration layer.
[0127] 2) 4N grade TaC was dissolved in an organic solvent to prepare a TaC-containing slurry, the slurry comprising: 32.7 parts of TaC powder, 25 parts of ethanol, 20 parts of tetrahydrofuran, 1.5 parts of BYK defoamer, 3.5 parts of cellulose ether, 10 parts of linear saturated aliphatic hydrocarbon, and 1.3 parts of carbon powder. After mixing and stirring the above components for 2.5 hours, the slurry was sprayed onto the surface of the graphite substrate with the TaxCy permeation layer using a sprayer. The sprayed graphite substrate was placed in a heating furnace, heated to 200°C in an air environment and dried for 10 hours. Thereafter, argon gas was introduced into the heating furnace, and the mixture was sintered at 800 mbar and 600°C for 4 hours. Subsequently, the pressure was increased to 1000 mbar, the temperature was increased to 1700°C, and the mixture was sintered for 9 hours. Finally, the pressure was increased to 150 kPa, the temperature was increased to 2300°C, and the mixture was sintered for 15 hours. Finally, the temperature was reduced to room temperature and atmospheric pressure after 20 hours to obtain crucible 1#.
[0128] Crucible 2#
[0129] 1) placing a tantalum pentachloride n-butanol solution soaked with a graphite substrate in a container, wherein the concentration of tantalum pentachloride in the tantalum pentachloride n-butanol solution is 70%, and the porosity of the graphite substrate is 45%. The container is placed in a pressure chamber for pressurization treatment at a pressurization rate of 0.2 MPa / min. When the pressure in the pressure chamber reaches 1 MPa, the pressure is maintained for 1 hour, and then the pressure is released. The soaked graphite substrate is transferred to a vacuum furnace and dried at 80°C for 5 hours. Then, a vacuum furnace is opened. Argon gas was introduced to maintain the pressure in the furnace at 800 mbar, and then calcination was carried out. The temperature was increased in a step-by-step manner: increased to 250°C in 1 hour and calcined for 6 hours; then increased to 850°C in 2 hours and calcined for 3.5 hours; finally increased to 1200°C in 1 hour and calcined for 5 hours; then the temperature was cooled in stages: cooled to 900°C in 1 hour and maintained for 2 hours, then cooled to 750°C in 1 hour and maintained for 1 hour, and finally cooled to room temperature at a rate of 15°C / h to obtain a graphite substrate with a TaxCy infiltration layer.
[0130] 2) 4N grade TaC was dissolved in an organic solvent to prepare a TaC-containing slurry, which included: 25 parts of TaC powder, 20 parts of ethanol, 25 parts of tetrahydrofuran, 3 parts of BYK defoamer, 2 parts of cellulose ether, 15 parts of linear saturated aliphatic hydrocarbon, and 3 parts of carbon powder. After mixing and stirring the above components for 2.5 hours, the slurry was sprayed onto the surface of the graphite substrate with the TaxCy permeation layer using a sprayer. The sprayed graphite substrate was placed in a heating furnace, heated to 180°C in an air environment and dried for 12 hours. After that, argon was introduced into the heating furnace and sintered at 700 mbar and 700°C for 3 hours. Subsequently, the pressure was increased to 1000 mbar, the temperature was increased to 1800°C, and sintered for 8 hours. Finally, the pressure was increased to 145 kPa, the temperature was increased to 2400°C, and sintered for 16 hours. Finally, the temperature was reduced to room temperature and atmospheric pressure after 25 hours to obtain crucible 2#.
[0131] Crucible 3#
[0132] 1) placing a tantalum pentachloride n-butanol solution soaked with a graphite substrate in a container, wherein the concentration of tantalum pentachloride in the tantalum pentachloride n-butanol solution is 70%, and the porosity of the graphite substrate is 45%. The container is placed in a pressure chamber for pressurization treatment at a pressurization rate of 0.05 MPa / min. When the pressure in the pressure chamber reaches 2 MPa, the pressure is maintained for 0.5 h, and then the pressure is released. The soaked graphite substrate is transferred to a vacuum furnace and dried at 60°C for 7 h, and then a vacuum furnace is introduced. Argon gas was used to maintain the pressure in the furnace at 1000 mbar before calcination. The temperature was raised in a step-by-step manner: raised to 350°C for 1 hour and calcined for 4 hours; then raised to 950°C for 2 hours and calcined for 2.5 hours; finally raised to 1300°C for 1 hour and calcined for 3 hours; then the temperature was lowered in stages: lowered to 1100°C for 1 hour and maintained for 0.5 hours, then lowered to 850°C for 1 hour and maintained for 0.5 hours, and finally cooled to room temperature at a rate of 25°C / h to obtain a graphite substrate with a TaxCy infiltration layer.
[0133] 2) 4N grade TaC was dissolved in an organic solvent to prepare a TaC-containing slurry, which included: 40 parts of TaC powder, 35 parts of ethanol, 15 parts of tetrahydrofuran, 1 part of BYK defoamer, 5 parts of cellulose ether, 5 parts of linear saturated aliphatic hydrocarbon, and 1 part of carbon powder. After mixing and stirring the above components for 2.5 hours, the slurry was sprayed onto the surface of the graphite substrate with the TaxCy permeation layer using a sprayer. The sprayed graphite substrate was placed in a heating furnace, heated to 220°C in an air environment and dried for 8 hours. After that, argon was introduced into the heating furnace, and sintered at 900 mbar and 500°C for 5 hours. Subsequently, the pressure was increased to 1100 mbar, the temperature was increased to 1600°C, and sintered for 10 hours. Finally, the pressure was increased to 155 kPa, the temperature was increased to 2200°C, and sintered for 14 hours. Finally, it was cooled to room temperature and normal pressure after 15 hours to obtain composite coating 3#.
[0134] Crucible 4#
[0135] The difference between this embodiment and crucible 1# is that in step 1), the graphite substrate was not subjected to gas pressurization treatment during immersion in the tantalum pentachloride n-butanol solution, but was only immersed at room temperature and pressure for 1 hour, followed by drying and calcination. The remaining conditions were the same as those for crucible 1#, resulting in crucible 4#.
[0136] Crucible 5#
[0137] The difference between this embodiment and crucible 1# is that in step 1), the soaked and dried graphite substrate is calcined in a vacuum furnace at 700°C for 7 hours while maintaining the furnace pressure at 900 mbar. The temperature is then gradually reduced at 1200°C for 5 hours. The remaining conditions are the same as those for crucible 1#, resulting in composite coated crucible 5#.
[0138] Crucible 6#
[0139] The difference between this embodiment and crucible 1# is that in step 2), the graphite substrate after spraying the slurry and drying is sintered in a heating furnace at 1000 mbar and 1200°C for 12 hours, then the pressure is increased to 140 kPa, the temperature is increased to 2300°C, and sintered for 20 hours. Finally, the temperature is cooled to room temperature and atmospheric pressure after 20 hours. The remaining conditions are the same as those for crucible 1#, thus producing crucible 6#.
[0140] Compare to Crucible D1#
[0141] Compared with Example 1, step 1) of this comparative example is the same as that of Example 1, and step 2) adopts the CVD method, specifically:
[0142] 2) will carry Ta x C y The graphite substrate of the infiltration layer was placed in a chemical vapor deposition furnace, evacuated to below 50 Pa, and then heated to 1200°C. A mixed gas consisting of ethane, TaCl5, H2 and carrier gas argon was introduced. The mixed gas maintained a stable flow rate into the deposition furnace, and the furnace pressure was maintained at 5000 Pa. The molar ratio of TaCl5 and ethane gas was first controlled at 1.2:1 to form a transition layer with a thickness of 50 μm; then the molar ratio of TaCl5 and ethane gas was controlled at 3:1 to form a TaC coating with a thickness of 60 μm, thus obtaining the comparative crucible D1#.
[0143] Compare to Crucible D2#
[0144] Compared with the comparative crucible D1#, this comparative example does not perform step 1), and only performs step 2) on the graphite substrate. In step 2), a transition layer and a TaC coating are formed on the graphite substrate by a CVD method. The specific CVD method conditions are the same as those for the comparative crucible D1#, that is, a comparative crucible D2# is prepared.
[0145] Compare to Crucible D3#
[0146] Compared with Example 1, this comparative example did not perform step 1), and only performed step 2) on the graphite substrate. The operating conditions of step 2) were the same as those in Example 1, so as to prepare a comparative crucible D3#.
[0147] High-temperature etching and thermochemical etching experiments were conducted on the crucibles 1#-6# and comparative crucibles D1#-D3# prepared above. The growth environment of third-generation semiconductor silicon carbide crystals using the PVT method was simulated. Crucibles 1#-6# and comparative crucibles D1#-D3# were exposed to 2300°C and etched in a silicon carbide atmosphere for 100 hours. The test results are shown in Table 1:
[0148] Table 1
[0149]
[0150]
[0151] In Table 1, the erosion weight loss rate = [(weight before the experiment - weight after the experiment) / weight before the experiment] × 100%. The high temperature erosion and thermochemical erosion experiments above demonstrate that the TaC coating of this embodiment can improve the protection of the graphite substrate, extend the tolerance and corrosion resistance of the TaC coating, and thus extend the service life of the crucible. SEM testing was performed on crucible 1# after multiple uses, and the results are as follows: Figure 3 , Figure 3 (a) is the test picture of the local composite coating on crucible 1#, Figure 3 (b) and Figure 3 (c) Figure 3 The enlarged view of the crack in (a) shows that even though the crucible 1# prepared in this embodiment has cracks after repeated use, the width of the cracks can be controlled within 1 μm and no through-cracks will form. It can still be used to produce high-quality silicon carbide crystals. x C y The permeation layer was characterized by EDS mapping and it was found that Ta x C y The permeation layer is formed inside and on the surface of the graphite substrate, and is interspersed with the inside of the graphite substrate, thereby having a strong bonding force with the graphite substrate, thereby improving the durability of the crucible. x C y XRD test of the penetration layer, TaC coating and TaC was performed. x C y Ta in the permeation layer x C y The grains grow anisotropically. The TaC grains of the TaC coating grow along the
[200] and
[220] directions.
[0152] The composite coating prepared in this embodiment is deposited on the surface of the graphite substrate, which can protect the graphite substrate and improve the temperature resistance and chemical corrosion resistance of the graphite substrate, thereby reducing the interference of the graphite substrate on the crystal growth environment and improving the stability of the crystal environment. x C y The oriented growth of grains in the infiltration layer and the TaC coating improves the density of the composite coating and can be used to prepare high-quality silicon carbide crystals.
[0153] Example 6
[0154] This embodiment relates to a method for preparing a silicon carbide single crystal with a diameter of 150 mm, comprising the following steps:
[0155] (1) Adding silicon carbide powder into a graphite crucible;
[0156] (2) Vacuum the furnace to 10-6 mbar, then introduce high-purity inert gas to 300-500 mbar, repeat this process 2-3 times, and finally evacuate the furnace to 10 -6 Below mbar;
[0157] (3) High-purity inert gas is introduced into the furnace body, and the pressure is raised to 10-100 mbar within 1-3 hours. The high-purity inert gas is continuously introduced and the pressure is maintained constant;
[0158] (4) Crystal growth stage: While maintaining the pressure constant, the temperature inside the furnace is raised to the single crystal growth temperature of 2200K-2800K within 3-5 hours, and the growth time is 30-150 hours;
[0159] (5) After the single crystal growth is completed, open the furnace body and take out the graphite crucible to obtain the silicon carbide single crystal.
[0160] Add equal amounts of silicon carbide powder to crucibles 1#-3# and comparative crucibles D1#-D3# prepared in Example 6; evacuate the furnace to 10 -6 mbar, and then introduce high-purity inert gas to 300mbar, repeat this process 3 times, and finally evacuate the furnace to 10 -6 mbar or less; introduce high-purity inert gas into the furnace body, increase the pressure to 30 mbar within 1 hour, and continue to introduce high-purity inert gas and maintain the pressure constant; crystal growth stage: while maintaining the pressure constant, increase the temperature in the furnace body to the single crystal growth temperature of 2500K within 3 hours, and the growth time is 70 hours; after the single crystal growth is completed, open the furnace body, take out the graphite crucible, and obtain silicon carbide single crystals 1#-3# and comparison silicon carbide single crystals D1#-D3#, respectively.
[0161] The above-mentioned silicon carbide single crystals 1#-3# and comparative silicon carbide single crystals D1#-D3# were subjected to the same cutting, grinding, mechanical polishing and chemical polishing to obtain silicon carbide substrates 1#-3# and comparative silicon carbide substrates D1#-D3#. In vivo stress testing was performed using the method of Examples 1-4. The results are shown in Tables 2 and 3.
[0162] Table 2
[0163]
[0164] Table 3
[0165]
[0166]
[0167] Surface shape inspection was performed on the silicon carbide substrates 1#-3#. The local thickness deviation of the silicon carbide substrates 1#-3# in the first gradient stress interval was within the range of 0.1-0.3 μm, the local thickness deviation in the second gradient stress interval was within the range of 0.3-0.7 μm, and the local thickness deviation in the third gradient stress interval was within the range of 0.7-2 μm.
[0168] The stress values in Tables 2-3 are all relative stress values. In this application, the positive and negative values in the stress values indicate whether the substrate is subjected to tensile or compressive stress. In the prior art, when describing and evaluating a substrate's stress state, the stress state is often determined by subtracting the minimum from the maximum stress value. For example, if the relative axial stress in the first gradient stress interval of SiC substrate 1# is -13.3 to 15.7, then this technique can also generally describe the relative axial stress in the first gradient stress interval of SiC substrate 1# as 29 MPa.
[0169] The data in Table 2-3 above are only for the substrates prepared by crucibles 1#-3# and comparative crucibles D1#-D3# prepared in Example 5. When the same crystal growth and processing methods as in Example 6 are used and crucibles 4#-8# are used to prepare silicon carbide substrates, and the parameters in Table 2-3 are characterized by absolute stress, the width of the third gradient stress interval extending inward from the edge of the substrate is 2.5-30 mm, the width of the second gradient stress interval extending inward from the edge of the third gradient stress interval is 10-50 mm; the relative stress in the body of the first gradient stress interval is greater than that of the equal stress interval. The relative internal stress in the second gradient stress interval is less than the relative internal stress in the third gradient stress interval; the radial internal relative stress in the first gradient stress interval is -15 to 15 MPa, the radial internal relative stress in the second gradient stress interval is -10 to 10 MPa, and the radial internal relative stress in the third gradient stress interval is -24.8 to 24.8 MPa; △S1≤△S2; 0MPa≤△S1≤10MPa, 0MPa≤△S2≤22MPa; △S3≤△S4; 0MPa≤△S3≤5MPa, 10MPa≤△S4≤2 0MPa; 0MPa≤S1-S2≤14.5MPa, 0MPa≤S3-S1≤22.5MPa; the axial internal relative stress in the first gradient stress interval is -20~20MPa, the axial internal relative stress in the second gradient stress interval is -16~16MPa, and the axial internal relative stress in the third gradient stress interval is -25~25MPa; 0MPa≤△S5≤10MPa, 0MPa≤△S6≤10MPa, 0MPa≤△S7≤10MPa; the internal absolute stress in the second gradient stress interval is greater than or equal to the first gradient stress interval. The internal absolute stress in the first gradient stress interval is -20 to 5 MPa, the internal absolute stress in the second gradient stress interval is 5 to 15 MPa, and the internal absolute stress in the third gradient stress interval is 15.2 to 50 MPa; the axial absolute stress in the first gradient stress interval is -30 to 10 MPa, the axial absolute stress in the second gradient stress interval is 10 to 30 MPa, and the axial absolute stress in the third gradient stress interval is 30.2 to 50 MPa.
[0170] The foregoing is merely an embodiment of the present application, and the scope of protection of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc. made within the technical ideas and principles of the present application should be included in the scope of protection of the present application.
Claims
1. A silicon carbide substrate with a stepped stress distribution, characterized in that: The silicon carbide substrate has a diameter of 150 mm or more, and includes a first main surface and a second main surface; The first major surface has a first gradient stress zone, a second gradient stress zone surrounding the first gradient stress zone, and a third gradient stress zone surrounding the second gradient stress zone, wherein the width of the third gradient stress zone extending inward from the edge of the substrate is 2.5-30 mm, and the width of the second gradient stress zone extending inward from the edge of the third gradient stress zone is 10-50 mm; The internal relative stress in the first gradient stress interval is greater than or equal to the internal relative stress in the second gradient stress interval, and less than the internal relative stress in the third gradient stress interval. The internal relative stress is a stress value measured vertically extending at least 3 μm from the first main surface or the second main surface into the silicon carbide substrate.
2. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein: the in-vivo absolute stress in the second gradient stress interval is greater than or equal to the in-vivo absolute stress in the first gradient stress interval and less than the in-vivo absolute stress in the third gradient stress interval, the in-vivo absolute stress being a stress value measured vertically extending at least 3 μm from the first main surface or the second main surface into the silicon carbide substrate; and / or At any plane parallel to the first main surface and / or the second main surface, the radial internal absolute stress in the first gradient stress interval is -20 to 5 MPa, the radial internal absolute stress in the second gradient stress interval is 5 to 15 MPa, and the radial internal absolute stress in the third gradient stress interval is 15.2 to 50 MPa.
3. The silicon carbide substrate with a stepped stress distribution according to claim 2, wherein: An axial test is performed by extending perpendicularly into the silicon carbide substrate from any point on the first major surface. The axial absolute stress in the first gradient stress interval is -30 to 10 MPa, the axial absolute stress in the second gradient stress interval is 10 to 30 MPa, and the axial absolute stress in the third gradient stress interval is 30.2 to 50 MPa.
4. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein: At any plane parallel to the first main surface and / or the second main surface, the radial internal relative stress in the first gradient stress interval is -15 to 15 MPa, the radial internal relative stress in the second gradient stress interval is -10 to 10 MPa, and the radial internal relative stress in the third gradient stress interval is -24.8 to 24.8 MPa.
5. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein: At any plane parallel to the first major surface and / or the second major surface, S max1 represents the maximum absolute value of the relative stress in the radial body within the first gradient stress interval, S max2 represents the maximum absolute value of the relative stress in the radial body within the second gradient stress interval, S max3 Represents the maximum absolute value of radial relative internal stress in the third gradient stress interval, △S1=S max1 -S max2 , △S2=S max3 -S max1 , △S1≤△S2.
6. The silicon carbide substrate with a stepped stress distribution according to claim 5, characterized in that: 0MPa≤△S1≤10MPa, 0MPa≤△S2≤22MPa.
7. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein: At any plane parallel to the first major surface and / or the second major surface, S min1 represents the minimum absolute value of the relative stress in the radial body within the first gradient stress interval, S min2 represents the minimum absolute value of the relative stress in the radial body within the second gradient stress interval, S min3 Represents the minimum absolute value of the relative stress in the radial body within the third gradient stress interval, △S3=S min1 -S min2 , △S4=S min3 -S min1 , △S3≤△S4.
8. The silicon carbide substrate with a stepped stress distribution according to claim 7, wherein: 0MPa≤△S3≤5MPa, 10MPa≤△S4≤20MPa.
9. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein At any plane parallel to the first main surface and / or the second main surface, S1 represents the average absolute value of the radial internal relative stress in the first gradient stress interval, S2 represents the average absolute value of the radial internal relative stress in the second gradient stress interval, and S3 represents the average absolute value of the radial internal relative stress in the third gradient stress interval. 0 MPa≤S1-S2≤14.5 MPa, and 0 MPa≤S3-S1≤22.5 MPa.
10. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein An axial test is performed by extending perpendicularly into the silicon carbide substrate from any point on the first major surface. The axial in-body relative stress in the first gradient stress interval is -20 to 20 MPa, the axial in-body relative stress in the second gradient stress interval is -16 to 16 MPa, and the axial in-body relative stress in the third gradient stress interval is -25 to 25 MPa.
11. The silicon carbide substrate with a stepped stress distribution according to claim 10, wherein: An axial test is performed vertically from any point of the first main surface into the silicon carbide substrate, S max5 It is recorded as the maximum relative stress in the axial body in the first gradient stress interval, S min5 It is recorded as the minimum relative stress in the axial body in the first gradient stress interval, △S5=S max5 -S min5 , 0MPa≤△S5≤10MPa; S max6 It is recorded as the maximum relative stress in the axial body in the second gradient stress interval, S min6 It is recorded as the minimum relative stress in the axial body in the second gradient stress interval, △S6=S max6 -S min6 , 0MPa≤△S6≤10MPa; S max7 It is recorded as the maximum relative stress in the axial body in the third gradient stress interval, S min7 It is recorded as the minimum relative stress in the axial body in the third gradient stress interval, △S7=S max7 -S min7 , 0MPa≤△S7≤10MPa.
12. The silicon carbide substrate with a stepped stress distribution according to claim 1, wherein The diameter of the silicon carbide substrate is greater than 200 mm, the width of the third gradient stress interval extending inward from the edge of the substrate is 21-30 mm, and the width of the second gradient stress interval extending inward from the edge of the third gradient stress interval is 10-39 mm; and / or The thickness of the silicon carbide substrate is not less than 0.1 mm.
Citation Information
Patent Citations
Small-angle silicon carbide crystal with few grain boundaries, substrate and preparation method thereof
CN113652749A
Silicon carbide crystal with annular morphology, preparation method thereof and prepared substrate
CN113652750A
Cited By
Silicon carbide substrate having stepwise stress distribution
EP4717801A1